Rujukan Fiqih Kontemporer Dalam Mengatasi Problematika Sosial Keagamaan di Kalangan Santri Milenial - Zaenal Arifin; Moh. Romli (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Studying the science of ushul fiqh in the pesantren tradition is significant for the discovery and formation of Islamic law. In fact, ushul fiqh is a mandatory subject that must be mastered by students from the Ibtidaiyah, Aliyah to Ma'had aly levels today. However, the majority of students who study ushul fiqh in Islamic boarding schools are stuck in a conservative paradigm, where studying ushul fiqh is only limited to something that is consumptive, read and memorized, without being contextualized and applied. In fact, Ushul fiqh must be able to be presented in the midst of society in a grounded logical and realistic manner, even ushul fiqh as the primary commodity of the santri in the methodology istinbat al-hukm must address the problems faced by contemporary society. That is the challenge for the students millennial generation in studying ushul fiqh today. In this paper, how to describe the activities of studentsnow salafiyah Islamic boarding schools (not salafi) in studying and understanding ushul fiqh with a descriptive-qualitative research approach model. So that what is studied in this paper is the paradigm of thinking in a community of millennial students in studying and developing ushul fiqh, when faced with social, cultural, political and economic environmental issues that require juridical Islamic law in the frame of religious texts. From the results of this discussion it can be seen that the millennial students' style of thinking in the development and dynamics model of ushul fiqh athoriqotul `Amala (work method) exploration of Islamic law is centered on; revitalization of ushul fiqh, text diversification (fahm nushus asy-syari'ah) and extension maqashid as-syari'ah, that is, the expansion in understanding the purpose of Sharia'h (Fahm maqashid as-syari'ah). Besides that, millennial students can use the ushul fiqh method as a methodthariqatu al a'mal, (work pattern). First, making maslahah a tool in setting the law.Second, match like the legal fatwa of the clergy, with the current situation and conditions.Third, operationalize Ushul Fiqh in Islamic law istinbat as a deductive method. And fourth, complete with Qawaid al-Fiqhiyyah. Keywords: ushul iiqh, social problems, millennial santi